Electronic structure calculations of ESR parameters of melanin units - Batagin Neto, Augusto [UNESP]; Uhle, Erika Soares Bronze [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Royal Soc Chemistry, 2015)
Melanins represent an important class of natural pigments present in plants and animals that are currently considered to be promising materials for applications in optic and electronic devices. Despite their interesting properties, some of the basic features of melanins are not satisfactorily understood, including the origin of their intrinsic paramagnetism. A number of experiments have been performed to investigate the electron spin resonance (ESR) response of melanin derivatives, but until now, there has been no consensus regarding the real structure of the paramagnetic centers involved. In this work, we have employed electronic structure calculations to evaluate the ESR parameters of distinct melanin monomers and dimers in order to identify the possible structures associated with unpaired spins in this biopolymer. The g-factors and hyperfine constants of the cationic, anionic and radicalar structures were investigated. The results confirm the existence of at least two distinct paramagnetic centers in melanin structure, identifying the chemical species associated with them and their roles in electrical conductivity.